Impact of New Technologies on Collection Development and Circulation in Special Libraries - Gowtham, M. S.; Raghavan, M. C. (Journal of Information and Knowledge, 1982)
Emerging technologies are not only influencing information storage and retrieval activity of the information centres, but also the basic policy and pattern of collection development and circulation in special libraries. The new form of documents and developments in information technology are changing the concept of document from printed to electronic form. These developments are a help to the user in getting access to the needed information on his table and avoids visit to libraries to collect the conventional documents. The paper highlights these aspects by reviewing the recent technological developments in the field of document production, computer and communication technologies.